THE CONCEPT OF CRITICAL EDUCATION IN FAZLUR RAHMAN'S THOUGHT: AN IMPLEMENTATION STUDY IN ISLAMIC EDUCATIONAL INSTITUTION - Bisana, Bambi; Saihan, Saihan; Muhith, Muhith; Rahman, Yudi Ardian (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to examine the implementation of the concept of critical education in Fazlur Rahman's thought at MAS Al-Islah Bondowoso and its impact on developing students' critical thinking skills within the context of Islamic education. This topic is significant as critical education plays a vital role in shaping a generation capable of analyzing and understanding Islamic teachings contextually. The research employs a qualitative approach with a case study design, collecting data through interviews, observations, and documentation conducted at the research site. The findings reveal that the implementation of critical education at MAS Al-Islah involves contextual understanding of Islamic teachings and learning methods that encourage discussion and critical analysis. However, challenges such as resistance to traditional teaching methods, time constraints, and limited resources were identified. Despite these challenges, the results show a positive impact of critical education, including improved analytical thinking and communication skills among students. The study concludes that critical education based on Fazlur Rahman's thought significantly contributes to the intellectual development of students and is relevant for broader application in Islamic education.